Clerodendrum fragrans (Vent) Willd: Tinjauan Farmakognosi-Fitokimia dan Farmakologi: Clerodendrum fragrans (Vent) Willd: Tinjauan Farmakognosi-Fitokimia dan Farmakologi - Donald Emilio Kalonio; Elisabeth Natalia Barung; Benedicta Irene Rumagit; Adeanne Caroline Wullur; Marco Antonio Timpalan (Yayasan Ahmad Mansyur Nasirah, 2022)
Introduction: Clerodendrum fragrans (Vent) Willd. was a plant that belongs to the genus Clerodendrum. Plants in this genus have unique species diversity with has wide therapeutic potential. The major phytochemical constituent of this plant was phenolic, flavonoid, terpenoid and steroid. This study was aimed to provide a systematic analysis review of the pharmacognosy-phytochemical aspects and pharmacological activities of C. fragrans (Vent) Willd. The research method was used a literature study. Scientific data searches were conducted on Google Scholar, PubMed, and ScienceDirect online databases using the keywords “Clerodendrum fragrans”, “Clerodendrum chinense”, and “Clerodendrum philippinum”. Based on the scientific data has obtained, the C. fragrans (Vent) Wild. was shown antidiabetic, antimicrobial, antioxidant, analgesic, antipyretic, anti-inflammatory and larvicidal activities. These results have confirmed the potential of C. fragrans (Vent) Willd. as an alternative treatment or as a drug's material resources through various in-vitro and in-vivo tests. Pendahuluan: Clerodendrum fragrans (Vent) Willd. adalah tanaman yang termasuk dalam genus Clerodendrum. Tanaman dalam genus ini memiliki keanekaragaman jenis yang unik, serta memiliki potensi pemanfaatan dalam terapi yang luas. Kandungan utama dari tanaman ini adalah fenolik, flavonoid, terpenoid dan steroid. Penelitian ini bertujuan untuk memberikan tinjauan analisis sistematis tentang aspek farmakognosi-fitokimia dan aktivitas farmakologi tanaman C. fragrans (Vent) Willd. Metode penelitian yang digunakan adalah studi literatur. Pencarian data ilmiah dilakukan pada database online Google Scholar, PubMed, dan ScienceDirect dengan menggunakan kata kunci “Clerodendrum fragrans”, “Clerodendrum chinense”, dan “Clerodendrum philippinum”. Berdasarkan data ilmiah yang diperoleh tanaman C. fragrans (Vent) Willd memiliki aktivitas aktivitas antidiabetes, antimikroba, antioksidan, analgesik, antipiretik, antiinflamasi dan larvasida. Hasil ini mengkonfirmasi potensi tanaman C. fragrans (Vent) Willd. sebagai alternatif pengobatan atau sebagai bahan baku obat melalui berbagai pengujian in-vitro dan in-vivo.